Pengaruh Pelaksanaan Rehabilitasi Narkotika Terhadap Penurunan Tingkat Residivisme Pada Pengguna Narkotika Di Indonesia - Gian Rakha Anggara; Rifky Hafiz Tryanda; Mohd Nur Hakim (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the impact of drug rehabilitation on reducing recidivism rates among drug users in Indonesia using a normative-juridical approach, enriched by empirical methods through a case study of the National Narcotics Agency (BNN) rehabilitation institution. The legal basis includes Law Number 35 of 2009 concerning Narcotics and Government Regulation Number 17 of 2021 concerning the Handling of Drug Addict Rehabilitation, which shifts the paradigm from a retributive to a restorative one. National Narcotics Agency data from 2020 to 2025 shows that conventional recidivism reaches 60 to 70 percent, but decreases to 30 to 40 percent in integrated rehabilitation programs such as the National Narcotics Agency Rehabilitation House and the Integrated Empowerment of Disabled Citizens Program. Determining factors for success include service accessibility, quality psychosocial therapy, post-rehabilitation monitoring, and cross-agency coordination. The findings confirm that rehabilitation is effective in reducing recidivism if supported by strong regulations and adequate funding. Recommendations include mandatory rehabilitation for non-drug users and reform of the 2023 Criminal Code to integrate restorative justice. This study contributes to the optimization of national anti-narcotics policy